2008
DOI: 10.1016/j.bbr.2007.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal exposure to 5-metoxytryptamine, behavioural-stress reactivity and functional response of 5-HT1A receptors in the adolescent rat

Abstract: Serotonin is involved in a wide range of physiological and patho-physiological mechanisms. In particular, 5-HT1A receptors are proposed to mediate stress-adaptation. The aim of this research was to investigate in adolescent rats: first, the consequences of perinatal exposure to 5-metoxytryptamine (5MT), a 5-HT1/5-HT2 serotonergic agonist, on behavioural-stress reactivity in elevated plus maze, open field and forced swim tests; secondly, whether the behavioural effects induced by perinatal exposure to 5MT on op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 61 publications
(90 reference statements)
1
17
1
1
Order By: Relevance
“…Serotonin exerts its influence in a number of behavioral and physiological processes in adult mammals (Cannizzaro et al, 2008; Donovan and Tecott, 2013). Some animal studies have demonstrated that interference in the serotoninergic system during pregnancy produces adverse neuroanatomic effects in the offspring, including reduced numbers of β‐adrenergic and serotoninergic receptors and abnormalities in brain serotonin receptor binding.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin exerts its influence in a number of behavioral and physiological processes in adult mammals (Cannizzaro et al, 2008; Donovan and Tecott, 2013). Some animal studies have demonstrated that interference in the serotoninergic system during pregnancy produces adverse neuroanatomic effects in the offspring, including reduced numbers of β‐adrenergic and serotoninergic receptors and abnormalities in brain serotonin receptor binding.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin exerts its influence in a number of behavioral and physiological processes in adult mammals (Cannizzaro et al, 2008;Lauder et al, 1988;Lisboa et al, 2007). Some animal researches have shown that affecting the serotoninergic system during pregnancy produce adverse neuroanatomic effects in the offspring, including reduced numbers of β-adrenergic and serotonin receptors and abnormalities in brain serotonin receptor binding.…”
Section: Discussionmentioning
confidence: 99%
“…Some animal researches have shown that affecting the serotoninergic system during pregnancy produce adverse neuroanatomic effects in the offspring, including reduced numbers of β-adrenergic and serotonin receptors and abnormalities in brain serotonin receptor binding. During embryogenesis, serotonin regulates axon growth, synaptogenesis, the development of γ-aminobutyric acid (GABA) and monoamine systems and is involved in cell migration (Cannizzaro et al, 2008;Lauder et al, 2000;Lisboa et al, 2007). One of the most abundant subtype receptors expressed in the mammalian brain is the 5-HT1A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies show that stressors acting upon the organism during pregnancy can have distinct and long lasting effects on the offspring. Prenatally stressed offspring may exhibit alterations in brain morphology and behavior (Pivina et al, 2007; Lee et al, 2007), increased emotional reactivity (Bosch et al, 2007; Cannizzaro et al, 2008) and altered regulation of the hypothalamic–pituitary–adrenal (HPA) axis (Weinberg et al, 2008). It was reported hyperactivity of HPA axis in offspring induced by prenatal stress (PNS) was related to the high levels of maternal corticosterone secretion during restraint stress (Maccari et al, 2003).…”
Section: Introductionmentioning
confidence: 99%